When the history of ideas meets theory: Arthur Lewis and the classical economists on development - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2017)
Lewis argued that his 1954 model of economic development in a dual economy was based on the classical framework originally advanced by Smith, Malthus, Ricardo and Marx. The present paper provides a detailed investigation of how Lewis adopted and adapted classical concepts such as productive/unproductive labor, economic surplus, subsistence wages, reserve army, capital accumulation etc. The Lewis 1954 model is set in the context of other growth and development models put forward at the time by Harrod, Domar, Swan, Kaldor, Solow, Nurkse, Rosenstein-Rodan, Myint and others. The heuristic role of the history of economic thought in Lewis's works is examined, as well as the influence of his LSE background. Lewis elaborated models of dual economies on both domestic and international levels, with distinct aims and results.
Keywords: B12; B29; B31; 330; Lewis; classical economics; dual economies; terms of trade; economic development